Tailored regulation: Will voluntary site-specific environmental performance standards improve welfare? - Allen Blackman; James Boyd (Fondazione Eni Enrico Mattei (FEEM), 2000)
Increasingly popular tailored regulation (TR) initiatives like EPA's Project XL allow plants to voluntarily substitute site-specific environmental performance standards for command-and-control regulations that dictate pollution abatement strategies. TR can significantly reduce participants' costs of complying with environmental regulations. But in doing so, it can also provide participants with a competitive advantage. We show that this can have undesirable welfare consequences when it enables relatively inefficient firms in oligopolistic markets to "steal" market share from more efficient firms. One critical determinant of whether or not TR has such adverse welfare impacts is the regulator's policy regarding the diffusion of TR agreements among non-participating firms.
Keywords: Q28; L13; L51; K32; 330; Tailored regulation; voluntary regulation; site-specific; performance standards; regulatory reform; Umweltstandard; Selbstverpflichtung; Folgekosten; Wohlfahrtsanalyse; Monopol; Duopol; Theorie